Exergy and Energy Analysis of Combustion of Blended Levels of Biodiesel, Ethanol and Diesel Fuel in a DI Diesel Engine. (25th April 2016) - Khoobbakht, Golmohammad; Akram, A.; Karimi, Mahmoud; Najafi, G.
Highlights: Exergy analysis showed that thermal efficiency of diesel engine was 36.61%. Energy loss and work output rates were 71.36 kW and 41.22 kW, respectively. Exergy efficiency increased with increasing engine load and speed. Exergy efficiency increased with increasing biodiesel and bioethanol. 0.17 L of biodiesel, 0.08 L of ethanol in 1 L of diesel at 1900 rpm and 94% load had maximum exergy efficiency. Abstract: In this study, the first and second laws of thermodynamics are employed to analyze the energy and energy in a four-cylinder, direct injection diesel engine using blended levels of biodiesel and ethanol in diesel fuel. Also investigated the effect of operating factors of engine load and speed as well as blended levels of biodiesel and ethanol in diesel fuel on the exergy efficiency. The experiments were designed using a statistical tool known as Design of Experiments (DoE) based on central composite rotatable design (CCRD) of response surface methodology (RSM). The resultant quadratic models of the response surface methodology were helpful to predict the response parameter (exergy efficiency) further to identify the significant interactions between the input factors on the responses. The results depicted that the exergy efficiency decreased with increasing percent by volume biodiesel and ethanol fuel. The fuel blend of 0.17 L biodiesel and 0.08 L of ethanol added to 1 L of diesel (equivalent with D80B14E6) at 1900 rpm and 94% load was realized have the most exergy efficiency. The results of energy and exergy analyses showed that 43.09% of fuel exergy was destructed and the average thermal efficiency was approximately 36.61%, and the exergetic efficiency was approximately 33.81%.